2020
DOI: 10.1002/ajim.23167
|View full text |Cite
|
Sign up to set email alerts
|

Radon and cancer mortality among underground uranium miners in the Příbram region of the Czech Republic

Abstract: Background This study aims to estimate the association between radon and site‐specific cancer mortality among a large contemporary cohort of male uranium miners. Methods Annual occupational radon exposure was estimated based on a worker's duration of underground mining in a year and estimates of potential alpha energy of radon progeny in their location of work. Cancer mortality over the period 1977‐1992 was ascertained for a cohort of 16 434 male underground uranium miners employed in the Czech Republic betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Neither occupational coexposures nor smoking were assessed in this analysis. Known occupational coexposures from uranium mining such as silica, arsenic, gamma radiation, long-lived radionuclides and diesel exhaust could influence rates of lung cancer 1 30. Other analyses have indicated that the influence of occupational coexposures on the radon–lung cancer risk is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Neither occupational coexposures nor smoking were assessed in this analysis. Known occupational coexposures from uranium mining such as silica, arsenic, gamma radiation, long-lived radionuclides and diesel exhaust could influence rates of lung cancer 1 30. Other analyses have indicated that the influence of occupational coexposures on the radon–lung cancer risk is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of occupational exposures have focussed on individuals working in the nuclear industry (including uranium workers [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and Chernobyl clean-up workers [7,63,64]), nuclear weapons testing programs [65][66][67][68][69][70][71], medical imaging [56,[72][73][74][75][76][77][78] or those working as airline crew [79][80][81][82][83][84]. Radiation exposures are typically fairly uniform, though highly protracted.…”
Section: Occupational Exposuresmentioning
confidence: 99%
“…The leukaemia SMR was reduced from 1.93 to 1.28 after excluding CLL. Studies of uranium miners and mill workers [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62], exposed to both low LET gamma and high LET alpha radiation, are similarly inconclusive. As with other industry nuclear workers, overall cancer rates tend not to be raised relative to the general population, although there are exceptions [52].…”
Section: Occupational Exposuresmentioning
confidence: 99%
“…In 2012, 17% of lung cancer cases in Alberta were found to be attributable to residential radon exposure [27]. Occupational exposure to high concentrations of radon has also been demonstrated to increase the risk of lung cancer in non-smokers [28], and the effects of occupational exposure to radon have also been described in the mining industry [29][30][31][32][33][34][35].and in other workplaces [36].…”
Section: Introductionmentioning
confidence: 99%